2013
DOI: 10.1097/ccm.0b013e3182711b38
|View full text |Cite|
|
Sign up to set email alerts
|

Resuscitation With Aged Blood Exacerbates Liver Injury in a Hemorrhagic Rat Model*

Abstract: Liver injury is exacerbated by the transfusion of stored blood, primarily due to the change in the rheological properties of RBC. This data call for clinical studies in patients undergoing liver resection or transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 36 publications
2
38
1
1
Order By: Relevance
“…It is thus logical to assess the effect of blood transfusion in the described rat model of PHx and bleeding. Indeed, this is the next step of our ongoing research, keeping in mind that previous studies from our lab showed blood transfusion to not always be beneficial to the liver (9, 10). Moreover, nowadays, restrictive blood-management protocols are endorsed, as reduced exposure to blood transfusions (with their inherent risks) results in improved patient safety and reduced costs (46).…”
Section: Discussionmentioning
confidence: 90%
“…It is thus logical to assess the effect of blood transfusion in the described rat model of PHx and bleeding. Indeed, this is the next step of our ongoing research, keeping in mind that previous studies from our lab showed blood transfusion to not always be beneficial to the liver (9, 10). Moreover, nowadays, restrictive blood-management protocols are endorsed, as reduced exposure to blood transfusions (with their inherent risks) results in improved patient safety and reduced costs (46).…”
Section: Discussionmentioning
confidence: 90%
“…3A) and by the percentage of UDC (fig. 3B) in the RBC population [5,18,31,32]. Figure 3A, depicting a representative ER curve, shows that cold storage induced an overall reduction in RBC deformability as shown by the shift of the St-RBC curve to lower ER values (elevation of the presence of low-deformable cells in the population) compared to F-RBC, and this was improved by rejuvenation.…”
Section: Resultsmentioning
confidence: 99%
“…In this method, applied to a maximum of less than 200 cells, the effects of surface area/volume ratios and of cytoplasmic viscosity on the overall RBC deformability are largely eliminated, causing the results to refer only to the membrane-specific changes that have occurred under cold storage and rejuvenation [40]. In our study, we measured the actual RBC deformability by direct visual monitoring of the changes in RBC shape under flow-induced shear stress, and the deformability parameters are derived from a large cell population (2,500 ± 300 cells), thereby enabling the derivation of parameters such as percentage of UDC, which better express St-RBC capacity to induced circulatory disorders [31,32]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These prepared RBCs were transfused to rats of a different cohort after hemorrhage. This practice is common (23, 24). In addition, mixing blood from different rats very rarely induces cell aggregation (25).…”
Section: Methodsmentioning
confidence: 99%